1995
DOI: 10.1128/aac.39.9.1979
|View full text |Cite
|
Sign up to set email alerts
|

Effect of levofloxacin on glycosaminoglycan and DNA synthesis of cultured rabbit chondrocytes at concentrations inducing cartilage lesions in vivo

Abstract: We investigated the toxic effect of levofloxacin (LVFX), a quinolone antibacterial agent, on cartilage by examining aspects of its in vivo toxicokinetics and effect on the function of cultured chondrocytes of the femoral articular cartilage from juvenile New Zealand White rabbits. Repeated administration of LVFX (100 mg/kg) orally for 7 days induced focal necrosis and superficial erosion in the articular cartilage of the femoral condyle, but 30 mg/kg did not. Concentrations of LVFX in the cartilage were highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 21 publications
3
37
0
Order By: Relevance
“…18,19 Thus, we assumed that genistein may inhibit synthesis of GAGs owing to impairment of expression of genes coding for one or more of enzymes involved in this process. Some data obtained by others in experiments on cancer cells could suggest that this might be the case; 20 -22 23 We found that genistein inhibited GAG synthesis significantly in both wild-type and MPS cells (Figure 1). The most effective inhibition was observed at concentrations of genistein about 10 -30 mM, and further increase in concentration of this isoflavone did not cause more pronounced effects (Figure 1 and data not shown).…”
Section: Resultsmentioning
confidence: 77%
“…18,19 Thus, we assumed that genistein may inhibit synthesis of GAGs owing to impairment of expression of genes coding for one or more of enzymes involved in this process. Some data obtained by others in experiments on cancer cells could suggest that this might be the case; 20 -22 23 We found that genistein inhibited GAG synthesis significantly in both wild-type and MPS cells (Figure 1). The most effective inhibition was observed at concentrations of genistein about 10 -30 mM, and further increase in concentration of this isoflavone did not cause more pronounced effects (Figure 1 and data not shown).…”
Section: Resultsmentioning
confidence: 77%
“…In an in vitro study using juvenile dog chondrocytes, nalidixic acid, ciprofloxacin, and three other quinolones inhibited mitochondrial dehydrogenase activity with inhibited proteoglycan synthesis 50 . Compromised mitochondrial integrities have also been shown in other in vitro experiments 51,52 . Changes in glycosaminoglycan and DNA synthesis and fibronectin-A single administration of pefloxacin to mice decreases biosynthesis of proteoglycan for the first 24 h, with recovery 48 h later.…”
Section: Cavity Formationmentioning
confidence: 68%
“…The decrease is also observed ex vivo, suggesting a direct effect of pefloxacin on this process, and a 10-day treatment induces oxidative damage in collagen, which may be induced by oxygen-derived reactive species in the extracellular matrix 53 . Moreover, in many in vitro and ex vivo studies, the cartilage of various animal species has exhibited inhibition of synthesis of either collagen or glycosaminoglycans 28,29,50,51,[54][55][56][57] or proteoglycan and DNA 28,[50][51][52]56 . An increase in fibronectin staining is observed in the vicinity of the cavity in the articular cartilage of juvenile dogs and rats receiving difloxacin and ofloxacin, respectively 41,42 .…”
Section: Cavity Formationmentioning
confidence: 99%
“…Supporting this hypothesis, several DNA synthesis inhibitors have been stated to increase in the incidence of cartilage lesions induced by the quinolone in rats [18]. In a more recent investigation using the cultured rabbit chondrocyte at concentrations inducing cartilage lesions, the quinolone inhibited glycosaminoglycan synthesis initially and DNA synthesis and mitochondrial function secondarily [11]. However, the precise mechanism of quinoloneinduced arthropathy remains unclear.…”
mentioning
confidence: 89%
“…However, quinolones have been reported to induce arthropathy in juvenile animals such as mice [12], rats [4,9,10], rabbits [11], dogs [3,5,8,20], nonhuman primates [17] and others [1,2] as a class effect of these derivatives. Among these species, the juvenile dog is thought to be most susceptible to articular cartilage lesions [6,19,20].…”
mentioning
confidence: 99%